2019
DOI: 10.2134/agronj2018.12.0779
|View full text |Cite
|
Sign up to set email alerts
|

Setting the Record Straight on Precision Agriculture Adoption

Abstract: Core Ideas There is a perception that adoption of precision agriculture has been slow.Precision agriculture is not one technology but a toolkit from which farmers choose what they need.Global Navigation Satellite Systems guidance is being adopted rapidly.Variable rate technology adoption rarely exceeds 20% of farms.Use of precision agriculture technology on non‐mechanized farms is almost nonexistent. There is a perception that adoption of precision agriculture (PA) has been slow. This study reviews the public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
161
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(173 citation statements)
references
References 46 publications
5
161
0
7
Order By: Relevance
“…The rates of adopters of CNT, CCs, and VRA were 61%, 40%, and 28%, respectively (Tables 1 and 2). The adoption rates in our study are similar to rates reported in recent studies (Lowenberg-DeBoer & Erickson, 2019;Miller, Griffin, & Ciampitti, 2019;Dunn et al, 2016). A study by Wade and Claassen (2017) reported higher CNT adoption rates in the Prairie Gateway, where Kansas is located, compared to other regions in the country.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The rates of adopters of CNT, CCs, and VRA were 61%, 40%, and 28%, respectively (Tables 1 and 2). The adoption rates in our study are similar to rates reported in recent studies (Lowenberg-DeBoer & Erickson, 2019;Miller, Griffin, & Ciampitti, 2019;Dunn et al, 2016). A study by Wade and Claassen (2017) reported higher CNT adoption rates in the Prairie Gateway, where Kansas is located, compared to other regions in the country.…”
Section: Resultssupporting
confidence: 90%
“…We examined the adoption timing of CNT, CCs, and VRA. We selected these practices because of the adoption gap (Carlisle, 2016;Lowenberg-DeBoer and Erickson, 2019) and the potential economic and environmental benefits these practices offer. Some of these benefits are improvements to soil productivity and health, the reduction of soil erosion and nutrient leaching, and cost savings (Blanco-Canqui, Mikha, Presley, & Claassen, 2011;Snapp et al, 2005).…”
Section: Methods and Datamentioning
confidence: 99%
“…Technologies in the PA tool box such as yield monitoring, Global Navigation Satellite Systems (GNSS), light bars, auto guidance, and variable rate devices enable farmers and researchers to conduct on‐farm experiments at a field scale, in multiple locations and at much lower cost. Extensive analyses of private and government survey data collected in different countries around the world showed that GNSS, sprayer boom control and planter shutoffs technologies have been adopted at the highest rates (Lowenberg‐DeBoer and Erickson, 2019). Surprisingly, variable rate technologies, one of the main and original components in the PA tool box, have not been widely adopted by farmers.…”
Section: Introductionmentioning
confidence: 99%
“…We developed a prototype of e-trap that had a high cost for materials (750 euros per trap) and associated software (2100 euros). Large-scale production of e-traps is considered to strongly decrease costs to the level that farmers will accept to adopt this technology, as other technologies have been rapidly adopted by the society (i.e., mobile phones or global navigation satellite systems) [50]. In this particular case of olive production in the Balearics, production plots are medium-or small-sized (2 to 10 h) and mostly lack public or private advisory system for pest control [7].…”
Section: Discussionmentioning
confidence: 99%